Clinical and epidemiological profiles of non-traumatic myelopathies - Wladimir Bocca Vieira de Rezende Pinto; Paulo Victor Sgobbi de Souza; Marcus Vinícius Cristino de Albuquerque; Lívia Almeida Dutra; José Luiz Pedroso; Orlando Graziani Povoas Barsottini (Arquivos de Neuro-Psiquiatria, 2016)
ABSTRACT Non-traumatic myelopathies represent a heterogeneous group of neurological conditions. Few studies report clinical and epidemiological profiles regarding the experience of referral services. Objective To describe clinical characteristics of a non-traumatic myelopathy cohort. Method Epidemiological, clinical, and radiological variables from 166 charts of patients assisted between 2001 and 2012 were compiled. Results The most prevalent diagnosis was subacute combined degeneration (11.4%), followed by cervical spondylotic myelopathy (9.6%), demyelinating disease (9%), tropical spastic paraparesis (8.4%) and hereditary spastic paraparesis (8.4%). Up to 20% of the patients presented non-traumatic myelopathy of undetermined etiology, despite the broad clinical, neuroimaging and laboratorial investigations. Conclusion Regardless an extensive evaluation, many patients with non-traumatic myelopathy of uncertain etiology. Compressive causes and nutritional deficiencies are important etiologies of non-traumatic myelopathies in our population.